PRICING TOOLS IN THE FRAMEWORK OF IMPROVING THE EFFICIENCY OF FINANCIAL MANAGEMENT AND SECURITY OF AN ENTERPRISE - SAVCHENKO, Olena; HREKOV, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The luck of understanding of the fundamental importance and key role of pricing instruments is a serious barrier that significantly limits the potential of companies to strategically build their financial strength and ensure long-term stability. This inevitably leads to a negative impact on profitability, creates significant difficulties in the effective cash flow management. This can be vital for operating activities, and critically reduces the overall ability of the company to withstand various financial threats and unforeseen crises. In modern fast-changing and highly competitive business environment, external and internal dangers can arise unexpectedly, so untimely or ineffective responses to these negative factors often result in catastrophic financial losses that can significantly in the long-term. At the same time, paradoxically, even small and seemingly imperceptible changes in the price of goods or services can cause huge fluctuations in the total income of an enterprise, and these variations can reach impressive levels of 20-50%, both in the positive direction, contributing to the growth of profits, and in the negative direction, leading to a significant decrease in profits. This fact underlines the extreme sensitivity of financial results to pricing policy. However, despite this obvious and statistically proven correlation between pricing and financial performance, only a tiny amount of the world's largest and most influential companies, namely about 5% of the prestigious Fortune 500, demonstrate an effective understanding and consistent use of optimal pricing as a strategic tool for maximising profits and ensuring sustainable financial development. This indicates a considerable untapped potential in pricing for most companies.The article provides a detailed study of the key pricing instruments that can be successfully applied by various enterprises in order to significantly improve the efficiency of their financial management and ensure an adequate level of financial security in the permanent uncertainty. Particular attention is paid to emphasising the crucial importance of careful differentiation of the choice and application of pricing instruments in accordance with specific factors that have a direct impact on the formation of prices in the market. In addition, the author emphasises the importance of integrating the latest information systems and technologies, including the power of artificial intelligence, into the process of prompt collection and comprehensive analysis of critical information on prices set by key competitors in the market. This allows businesses to make more informed and timely decisions about their pricing policy.The authors of the article consistently emphasise the necessity to consider the pricing process not as a static function, but as a complex, multifaceted and dynamic process that is constantly evolving under the influence of various internal and external factors. In this regard, there is an urgent need to develop and implement a flexible and adaptive progressive pricing mechanism that would meet the modern requirements of a market economy, take into account the changing consumer preferences, technological innovations and strategies of competitors, and ensure a sustainable financial position of the enterprise in the long term. Such a mechanism should be based on in-depth data analysis, forecasting of market trends and prompt response to any changes in the business environment.
Keywords: pricing; financial management; enterprise security; pricing methods; pricing risks; pricing mechanism